Gambaran Grit Pada Mahasiswa di Indonesia - Lie Fun Fun; Hera Lestari Mikarsa; Dian Kemala Putri (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
This study aims to provide an overview of grit among Indonesian university students with quantitative design. The respondents in this study were 720 individuals selected through purposive sampling and surveyed online using a Google Form. The research design used in this study was descriptive quantitative analysis, employing the Grit-S questionnaire. The results of this study showed that 45.4% of students had high grit, 39.9% had low grit, 10.1% had very high grit, and 4.6% had very low grit. Additionally, no significant differences were found in grit scores between genders or academic fields such as medicine, science and technology, and social sciences and humanities. However, a difference in grit scores was found between students enrolled in Public and Private Universities; Private Universities scored slightly higher than Public Universities. The variations in grit levels among students can be used as a reference for counselors to provide guidance to students who exhibit low levels of grit. Furthermore, this finding highlights the need for further research to identify factors that may influence grit levels among university students in Indonesia.